Mito e concretude: a morte na poesia de Angelus Silesius - Nascimento, Darlan Xavier [UNESP]; Maas, Wilma Patricia Marzari Dinardo [UNESP] (My University, 2012)
This study intends to get a general overview on the German Angelus Silesius (1624- 1677)’s poetry about the way he discusses death. For the purpose of postulating some hypotheses about the meaning of death in the historical period in which the poet lived, we will comment some poems by identifying clues which reclaim the period’s moral.

Este trabalho pretende levantar um panorama geral da poesia do alemão Angelus Silesius (1624-1677) no que diz respeito à discussão sobre a temática da morte. A fim de postular algumas hipóteses sobre o significado da morte no período histórico em que o poeta viveu, comentaremos alguns poemas, identificando pistas que retomem a moral da época.
Myth and concreteness: death in Angelus Silesius’s poetry
Keywords: Angelus Silesius; death; Christianity; 17th century; Angelus Silesius; poesia mística; morte; Cristianismo; século XVII